Islamic Law and Customs Interface: A Juridical Analysis - Ibrahim Hassan Sulaiman (Maklumat: Journal of Da'wah and Islamic Studies, 2025)
Islamic law is a unique and dynamic system which derives its laws from many sources which included primary, secondary and what is known as auxiliary sources. Customs or al-‘Urf of people is accepted as a source of law by some schools of law based on Qur’an and Sunnah injunctions. The Muslim jurist or judge, must take into consideration customs of people and their local practices in deciding cases or issuing Fatwa. This research elucidated on the importance of customs, sources, divisions, and conditions of its acceptability as a law. The research maintained that the Maliki school of law which is the prevalent Madhhab in Nigeria, extensively considers customs as a source of law especially in adjudicating of cases in Shari’ah courts of law.